Sustainable transport for Chinese cities - Mackett, R. L.; May, A. D. 1944-; Kii, Masanobu (Transport and sustainability ;, 2013)
The volume is based on papers presented at a workshop on the green transport agenda and its implications for Chinese cities, organised by the World Conference on Transport Research Society in September 2010. The five sections of this volume review the challenges facing urban transport internationally and in China. It considers approaches to policy formulation, the challenge of urban mobility and the development of green sustainable transportation, by reviewing best practice in objective setting, strategy analysis and policy selection, and comparing these with current practice in China. The authors examine passenger transport, and consider a number of current policy interventions in China and compare these with western experience with demand management and new vehicle technologies. Topics include 5D land-use transport model for a high density, rapidly growing city and Contextual requirements for electric vehicles in developed and developing countries. Finally freight and logistics is addressed, including the role of freight villages and milk run strategies, and challenges and policy recommendations for road freight in Shanghai.